“One-Eyed Dragon” Li Keyong in the Historical and Fictional Literature of China in the Song Era (X—XIII Centuries) - A. G. Nesterov; I. R. Tretyak (Научный диалог, 2020)
The features of the reflection of the ruler of the Turks Shatuo Li Keyong (856—908, ruler in 887—908) activities in the Chinese literature of the Song era (X—XIII centuries) are examined in the article. It is shown that the deeds of Li Keyong found a detailed reflection in the historical chronicles and treatises dedicated to the period of the Five Dynasties and Ten Kingdoms (907—979), primarily “Jiu Wu-dai shi” and “Zizhi tongjian”. It is noted that the author of the most famous art-historical work “The newly compiled pinghua on the history of the Five Dynasties” describes in detail the activities of Li Keyong: he shows the Shatuo Turks as a people supporting Chinese cultural and political traditions and in many respects defending the Chinese traditional statehood. It is indicated that Li  Keyong actually became the founder of the Turkic-Chinese empire of the Late Tang and was considered in the historical and fiction literature as a consistent defender of the Chinese statehood. It is proved that Li Keiong was perceived by the author of pinghua, following the authors of the historical work “Zizhi tongjian”, as a defender of Chinese statehood and Chinese political tradition, and not as a stranger, despite his Turkic origin.